K Korelasi Komunikasi Terapeutik Perawat Dengan Tingkat Kepuasan Keluarga Pasien ICU - Novia Heriani; Clarissa Maharani Gandi (Journal of Nursing Invention, 2022)
Background: One of the central services in hospitals is the Intensive Care Unit (ICU). Where the ICU has nurses and special equipment intended for observation, care and therapy of patients suffering from critical, or potentially life-threatening illnesses with a prognosis that can still be expected. Patient and family satisfaction is a measure of service quality and the provision of care information in the ICU where one of the indicators is therapeutic communication. Objective: The purpose of this study was to determine whether there is a correlation between therapeutic communication and the level of family satisfaction of ICU patients at Ulin Hospital Banjarmasin. Method: This study uses an analytical research design with a cross sectional approach. The population in this study were the entire patient's family in the ICU Room of Ulin Hospital Banjarmasin in May-June 2022. Sampling with saturated samples, totaling 69 respondents. Collecting data using a nurse therapeutic communication questionnaire and patient's family satisfaction with the Spearman Rank statistical test. Result: The results of statistical tests obtained p value (0.000) < (0.05) so it can be concluded that there is a correlation between therapeutic communication and patient family satisfaction in the ICU room at Ulin Hospital Banjarmasin with a spearman rank value of 0.670 which indicates a positive correlation direction and the relationship between the two variables very strong. Conclusion: nurses must have the ability to carry out good therapeutic communication so that patient family satisfaction continues to increase.